Assessing the consequences of second-generation bioenergy crops for grain/livestock farming on the Canadian prairies: An agent-based simulation. Issue 2 (4th March 2023) - Anderson, Leigh; Schoney, Richard; Nolan, James
ABSTRACT: In North America, alternative energy policies have been mostly focused on first-generation biofuels. There is continued development of second-generation biofuels (SGB), crops founded upon low-value feedstocks thriving on marginal (low quality) land. SGB's alter the farming decision environment since they do not compete directly with high-value annual crops. To examine possible future consequences of SGB's on mixed farming, we develop anagent-based simulation model (ABM) of a major agricultural region in Western Canada. If energy prices for SGB's rise high enough, there will likely be structural changes in the sector. Farmers with significant quantities of marginal land experience the greatest benefit adopting energy crops. Spillover effects of energy crop adoption will also be felt in the beef industry since cattle numbers will be gradually reduced. Simulation results also indicate that beef farmers are better off with SGB crops since energy crops stabilise farm income as average farm size decreases.